Artistry in Bronze: The Greeks and Their Legacy XIXth International Congress on Ancient Bronzes - Kenneth Lapatin (Getty Publications, 2017)
The papers in this volume derive from the proceedings of the nineteenth International Bronze Congress, held at the Getty Center and Villa in October 2015 in connection with the exhibition Power and Pathos: Bronze Sculpture of the Hellenistic World. The study of large-scale ancient bronzes has long focused on aspects of technology and production. Analytical work of materials, processes, and techniques has significantly enriched our understanding of the medium. Most recently, the restoration history of bronzes has established itself as a distinct area of investigation. How does this scholarship bear on the understanding of bronzes within the wider history of ancient art? How do these technical data relate to our ideas of styles and development? How has the material itself affected ancient and modern perceptions of form, value, and status of works of art?